If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -4) + -5 = 2(2 + -1x) Reorder the terms: 3(-4 + 3x) + -5 = 2(2 + -1x) (-4 * 3 + 3x * 3) + -5 = 2(2 + -1x) (-12 + 9x) + -5 = 2(2 + -1x) Reorder the terms: -12 + -5 + 9x = 2(2 + -1x) Combine like terms: -12 + -5 = -17 -17 + 9x = 2(2 + -1x) -17 + 9x = (2 * 2 + -1x * 2) -17 + 9x = (4 + -2x) Solving -17 + 9x = 4 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -17 + 9x + 2x = 4 + -2x + 2x Combine like terms: 9x + 2x = 11x -17 + 11x = 4 + -2x + 2x Combine like terms: -2x + 2x = 0 -17 + 11x = 4 + 0 -17 + 11x = 4 Add '17' to each side of the equation. -17 + 17 + 11x = 4 + 17 Combine like terms: -17 + 17 = 0 0 + 11x = 4 + 17 11x = 4 + 17 Combine like terms: 4 + 17 = 21 11x = 21 Divide each side by '11'. x = 1.909090909 Simplifying x = 1.909090909
| 21x^2=-11x+40 | | 293=4(x)+3 | | 3/48=(1/2)n | | 7(x+2)-3x-1=6(x+4)-4x+3 | | 36x^2+x-117=0 | | 4(3.75)-5(2.5)=4 | | 4+5y=-2y+18 | | 2x-3-4x=5 | | x^2+x=x^2-2x+6 | | (4/6)x=(5/6)y | | (4/6)x(5/6)y | | (X-3)(2x+9)=9(3x+2) | | y-10=9y-6 | | ml=7.3l | | 9w=2*9w | | 4cosx-2=cosx | | 2^-1=1/64 | | 9x^2-9x-15=0 | | 6+2x+3y=48 | | 7b+2a-(3a+2b)= | | 4x-6=2(x+1) | | (X-786)(x+4)=0 | | (X-393)(x+4)=0 | | 2x+5(2.5)=20 | | 27=(27-15x)*2 | | 5779/19= | | -100=0.1x(30+-1x) | | -100=0.1(30-x) | | arccos(3/5) | | 4--7= | | 65+70=78 | | 12/x=6/11 |